Revascularization of decellularized lung scaffolds: principles and progress - Stabler, Collin T. (Am J Physiol Lung Cell Mol Physiol, 2015)
There is a clear unmet clinical need for novel biotechnology-based therapeutic approaches to lung repair and/or replacement, such as tissue engineering of whole bioengineered lungs. Recent studies have demonstrated the feasibility of decellularizing the whole organ by removal of all its cellular components, thus leaving behind the extracellular matrix as a complex three-dimensional (3D) biomimetic scaffold. Implantation of decellularized lung scaffolds (DLS), which were recellularized with patient-specific lung (progenitor) cells, is deemed the ultimate alternative to lung transplantation. Preclinical studies demonstrated that, upon implantation in rodent models, bioengineered lungs that were recellularized with airway and vascular cells were capable of gas exchange for up to 14 days. However, the long-term applicability of this concept is thwarted in part by the failure of current approaches to reconstruct a physiologically functional, quiescent endothelium lining the entire vascular tree of reseeded lung scaffolds, as inferred from the occurrence of hemorrhage into the airway compartment and thrombosis in the vasculature in vivo. In this review, we explore the idea that successful whole lung bioengineering will critically depend on 1) preserving and/or reestablishing the integrity of the subendothelial basement membrane, especially of the ultrathin respiratory membrane separating airways and capillaries, during and following decellularization and 2) restoring vascular physiological functionality including the barrier function and quiescence of the endothelial lining following reseeding of the vascular compartment. We posit that physiological reconstitution of the pulmonary vascular tree in its entirety will significantly promote the clinical translation of the next generation of bioengineered whole lungs.